XRCC1 protein; Form and function - Caldecott, Keith W (DNA repair, 2019)
The human gene that encodes XRCC1 was cloned nearly thirty years ago but experimental analysis of this fascinating protein is still unveiling new insights into the DNA damage response. XRCC1 is a molecular scaffold protein that interacts with multiple enzymatic components of DNA single-strand break repair (SSBR) including DNA kinase, DNA phosphatase, DNA polymerase, DNA deadenylase, and DNA ligase activities that collectively are capable of accelerating the repair of a broad range of DNA single-strand breaks (SSBs). Arguably the most exciting aspect of XRCC1 function that has emerged in the last few years is its intimate relationship with PARP1 activity and critical role in preventing hereditary neurodegenerative disease. Here, I provide an update on our current understanding of XRCC1, and on the impact of hereditary mutations in this protein and its protein partners on human disease.
Keywords: DNA double-strand break (DSB); Double-strand break repair (DSBR); DNA Breaks, Single-Stranded; DNA; DNA Repair; Non-homologous end-joining (NHEJ); protein XRCC1; Animals; Humans; jednořetězcové zlomy DNA; DNA single-strand break (SSB); lidé; X-ray Repair Cross Complementing Protein 1; DNA Breaks, Double-Stranded; zvířata; Single-strand break repair (SSBR); dvouřetězcové zlomy DNA; oprava DNA